The Principle of ats-Tsabit bi al-‘Urfi ka ats-Tsabit bi asy-Syar’i in DSN-MUI Fatwa No. 117 on Sharia Fintech - Bianda, Ryan (IAIN Syekh Nurjati Cirebon, 2024)
This research aims to describe and analyze the integration of the fiqh rule Ats-Tsabit bi Al-‘Urfi ka Ats-Tsabit bi Asy-Syar’i into the context of DSN-MUI Fatwa No. 117, which regulates Sharia-compliant financial technology (fintech). The study highlights the significance of combining urf (custom) and Sharia principles to create a comprehensive framework for enhancing Islamic financial products and services. This qualitative research uses a literature-based approach, collecting secondary data from fatwas, books, journals, and other relevant sources. The findings reveal that the application of the Ats-Tsabit rule not only reinforces the validity of modern financial transactions in compliance with Sharia but also supports the innovation needed to address the dynamic demands of society. The study also emphasizes the role of urf as a fundamental element in bridging traditional Islamic law with contemporary economic practices. These insights provide actionable recommendations for improving regulatory frameworks and fostering public trust in the Islamic fintech ecosystem. This research makes a significant contribution to the development of Islamic economic law by offering a sustainable approach to aligning technological advancements with Sharia principles.Keywords: Financial Technology, Fatwa, DSN-MUI, Islamic Law, Urf.